Health Care Professionals' Views on Using Remote Measurement Technology in Managing Central Nervous System Disorders: Qualitative Interview Study - Andrews, Jacob A; Craven, Michael P; Jamnadas-Khoda, Jennifer; Lang, Alexandra R; Morriss, Richard; Hollis, Chris (JMIR Publications, 2020)
BackgroundRemote measurement technologies (RMT) can be used to collect data on a variety of bio-behavioral variables, which may improve the care of patients with central nervous system disorders. Although various studies have explored their potential, prior work has highlighted a knowledge gap in health care professionals' (HCPs) perceptions of the value of RMT in clinical practice. ObjectiveThis study aims to understand HCPs' perspectives on using RMT in health care practice for the care of patients with depression, epilepsy, or multiple sclerosis (MS). MethodsSemistructured interviews were conducted with 26 multidisciplinary primary and secondary care HCPs who care for patients with epilepsy, depression, or MS. Interviews were transcribed verbatim and analyzed using thematic analysis. ResultsA total of 8 main themes emerged from the analysis: (1) potential clinical value of RMT data; (2) when to use RMT in care pathways; (3) roles of health care staff who may use RMT data; (4) presentation and accessibility of data; (5) obstacles to successful use of RMT; (6) limits to the role of RMT; (7) empowering patients; and (8) considerations around alert-based systems. ConclusionsRMT could add value to the system of care for patients with central nervous system disorders by providing clinicians with graphic summaries of data in the patient record. Barriers of both technical and human nature should be considered when using these technologies, as should the limits to the benefits they can offer.